The handbook of competency mapping understanding, designing and implementing competency models in organizations - Sanghi, Seema 1961- (Los Angeles, California SAGE Publications, Inc., 2016)
This thoroughly revised third edition helps human resource managers and professionals understand, develop, manage and map competencies within their organizations. It presents the complete know-how of developing competency framework in detail. In this edition, several chapters have been expanded to provide a greater understanding of business strategies, environmental imperatives and the changing role of HR as a strategic partner. Developed over years of research and consultancy experience, three new chapters on 'Competency-based Interviewing', 'Writing Competencies' and 'Competency Framework for Academic Institutions' have been added
Title from title screen (viewed October 20, 2023)
Includes bibliographical references and index
Description based on XML content
Keywords: Core competencies; Management; Organizational effectiveness; Strategic planning; Employees -- Training of